2015
DOI: 10.3390/toxins7051808
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Honeybee Sting on Peptidome Profile in Human Serum

Abstract: The aim of this study was to explore the serum peptide profiles from honeybee stung and non-stung individuals. Two groups of serum samples obtained from 27 beekeepers were included in our study. The first group of samples was collected within 3 h after a bee sting (stung beekeepers), and the samples were collected from the same person a second time after at least six weeks after the last bee sting (non-stung beekeepers). Peptide profile spectra were determined using MALDI-TOF mass spectrometry combined with Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(36 reference statements)
0
10
0
1
Order By: Relevance
“…Generation of a QC model is based on storing the class averages of the peak areas together with p-values obtained from a t -test. First, the peak areas or intensities are sorted per peak and next a weighted average from all peaks need to be calculated [ 59 , 61 ]. SNN algorithm uses a prototype-based classification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of a QC model is based on storing the class averages of the peak areas together with p-values obtained from a t -test. First, the peak areas or intensities are sorted per peak and next a weighted average from all peaks need to be calculated [ 59 , 61 ]. SNN algorithm uses a prototype-based classification.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristic spectra of each study class, which are named prototypes, are identified. Then, they are considered as prototypical samples of that class from a proteomic point of view [ 59 , 61 ]. Two indicators of the model’s performance, 20% leave one out cross validation (10 iterations) and recognition capability, were calculated for all three used algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…apaminę, która jest neurotoksyną, peptydy niszczące (degranulujące) komórki tuczne, wazoaktywne aminy oraz białka enzymatyczne, np. hialuronidazę czy fosfolipazę (18). Melityna ma właściwości hemolityczne.…”
Section: Discussionunclassified
“…Serum peptides can be used to distinguish a normal, healthy individual from someone who has recently been stung by a wasp [19]. After analyzing the serum levels of 34 amino acids, Matysiak et al demonstrated that the levels of L-glutamine (Gln), L-glutamic acid (Glu), L-methionine (Met), and 3-methyl-L-histidine (3MHis) were significantly different between wasp sting victims and healthy controls [20].…”
Section: Introductionmentioning
confidence: 99%